Analisis Implementasi Nilai-nilai Kearifan Lokal Dayak dalam Kurikulum Merdeka di Sekolah Dasar Negeri Kabupaten Pulang Pisau Kalimantan Tengah - Cynthia Cynthia; Ahmad Syari; M. Fatchurahman (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to analyze the implementation of Dayak local wisdom values in the Merdeka Curriculum at public elementary schools in Pulang Pisau Regency, Central Kalimantan. Dayak local wisdom, which encompasses values such as mutual cooperation, solidarity, tolerance, environmental awareness, and respect for cultural traditions, plays a significant role in shaping students' character amid the challenges of globalization and the disruptive era. This research employs a qualitative approach using a case study method. The research participants include school principals, teachers, students, and educational stakeholders from several public elementary schools in Pulang Pisau Regency. Data are collected through observations, in-depth interviews, documentation, and literature reviews. Data analysis is conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings are expected to provide a comprehensive description of how Dayak local wisdom values are integrated into the planning, implementation, and evaluation of learning activities within the Merdeka Curriculum framework. Furthermore, the study seeks to identify supporting and inhibiting factors affecting the implementation of local wisdom in educational practices and to formulate strategic recommendations for strengthening character education and preserving local culture in elementary schools. The results are expected to serve as a reference for educational policy development that promotes cultural preservation and enhances the quality of learning in accordance with the socio-cultural context of local communities.